(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article on modern linguistics pays great attention to the interaction between the sound aspect of language and its aesthetic function, especially in poetic texts. Poetry, as a vocal activity, has special expressive means, among which vowel phonemes play an important role, forming the rhythmic and melodic structure of the text. The sound of a poem is not just a background decoration of the content, but an active element of artistic expression, influencing the reader’s perception.